2012
DOI: 10.2494/photopolymer.25.693
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Kinetics in Polymer-Bound and Polymer-Blended Photo-Acid Generators

Abstract: In the fabrication beyond 16 nm node, the uniform distribution of acid generators in resist matrix is a serious concern. Recently, the incorporation of acid generators to polymers via covalent bonds has attracted much attention in order to overcome the compatibility problem of acid generators with polymers and reduce the diffusion lengths of acid, which leads to high resolution and low line edge roughness (LER). However, understanding of the resist dissolution kinetics in polymer-bounded and polymer-blended ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the other hands, the bound resist is not a mixture, because the PAG unit is contained in the base polymer. The difference of the blend and bound resists has been reported by many researchers [10][11][12][13][14][15][16][17][18], and especially, Watanabe et al have reported that the bound resist is more less line edge roughness (LER) than blend resist [11]. The reason of low LER for bound resist is expected that the uniformity of bound resist is better than blend one, however, the chemical composition distribution analysis has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hands, the bound resist is not a mixture, because the PAG unit is contained in the base polymer. The difference of the blend and bound resists has been reported by many researchers [10][11][12][13][14][15][16][17][18], and especially, Watanabe et al have reported that the bound resist is more less line edge roughness (LER) than blend resist [11]. The reason of low LER for bound resist is expected that the uniformity of bound resist is better than blend one, however, the chemical composition distribution analysis has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] In particular, polymer-bound photoacid generators (PAGs) (anion bound) are actively investigated as EUV resists. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Many experimental results have shown that polymerbound PAGs have higher resolution than conventional resists (polymer-blend PAGs). On the other hand, the sensitivities of polymer-bound PAGs (anion bound) and polymer-blend PAGs are almost the same.…”
Section: Introductionmentioning
confidence: 99%